Protective effect of Juzen-taiho-to on hepatocarcinogenesis is mediated through the inhibition of Kupffer cell-induced oxidative stress - Tsuchiya, Masato (2008)
Traditional herbal formulations, such as Juzen-taiho-to (TJ-48), are used extensively in medical practice in Asia even though their mechanism of action remains elusive. This study tested a hypothesis that TJ-48 is protective against hepatocarcinogenesis by impeding Kupffer cell-induced oxidative stress. Forty-eight patients were randomly assigned to receive TJ-48 (n = 10), or no supplementation (n = 38) for up to 6 years after surgical treatment for hepatocellular carcinoma (HCC). In addition, to investigate the mechanism of protective action of TJ-48, diethylnitrosamine-containing water was administered for 22 weeks to male mice that were fed regular chow or TJ-48-containing diet. Liver tumor incidence, cell proliferation, number of 8-hydroxy-2′-deoxyguanosine-or F4/80-positive cells, and cytokine expression were evaluated. Although most of the patients experienced recurrence of HCC, a significantly longer intrahepatic recurrence-free survival was observed in the TJ-48 group. In mice, TJ-48 inhibited the development of liver tumors, reduced oxidative DNA damage, inflammatory cell infiltration and cytokine expression. Administration of TJ-48 improves intrahepatic recurrence-free survival after surgical treatment of hepatocellular carcinoma. On the basis of animal experiments, we reason that the protective mechanism of TJ-48 involves inhibition of Kupffer cells. This leads to lower levels of pro-inflammatory cytokines and oxidants in liver which may slow down the process of hepatocarcinogenesis and improves hepatic recurrence-free survival in patients with HCC.